Representasi Permasalahan Lingkungan dalam Buku Teks IPS Geografi SMP Kelas VII Kurikulum 2013 Edisi Revisi - M Iqbal Liayong Pratama; Een Syaputra; Hamengkubuwono Hamengkubuwono (UIN Fatmawati Sukarno Bengkulu, 2021)
This article aims to: 1) identify environmental themes in the social studies textbook for class VII SMP Curriculum 2013; and 2) analyzing the representation of environmental problems in the social studies textbook material for Class VII Junior High School Curriculum 2013. This research was conducted using qualitative methods. The research object was the social studies textbook material for class VII class VII curriculum 2013 revised edition published by the Ministry of Education and Culture in 2014. Data collection and data analysis were carried out using content analysis techniques. Based on the research conducted, it was found that: 1) there were as many as eight themes about the environment in the Social Science textbook for Class VII Curriculum 2013; 2) Of the eight themes concerning the environment, there are only a few themes that present environmental issues. Most of the other themes, although discussing the environment, do not present environmental issues at all. Some of the existing environmental problems are: river damage, forest destruction, and air and water pollution.